Antioxidant Properties of Methanolic Extract of Dolichos biflorus (Linn.) - KOTTAI MUTHU, A.; SETHUPATHY, S.; MANAVALAN, R.; KARAR, P.K. (Asian Journal of Chemistry, 2010)
The present study was conducted to evaluate the in vitro and in vivo antioxidant properties of methanolic extract of Dolichos biflorus (Linn.). The in vitro antioxidant potential of the plant extract was evaluated using three separate methods namely inhibition of free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), H2O2 assay and nitric oxide radical inhibition assay. Rabbits were fed high fat diet and the oxidative damage was explored by assessing parameters such as superoxide dismutase (SOD) gluthathione peroxidase (GPx) and gluthathione S-transferase (GST) in liver, heart and aorta. The effect of co-administration of two different doses (200mg/kg and 400 mg/kg body weight) of Dolichos biflorus extracts on the above parameters was also investigated and compared with standard drug atorvastatin. The in vitro antioxidant potential of methanolic extract of Dolichos biflorus when compared with the standard antioxidant like ascorbic acid, rutin, BHT exerted remarkable antioxidant activity. Antioxidant enzymes such as SOD, GPx and GST too showed enhanced activities on co-administration of methanolic extract of Dolichos biflorus. Higher dose of the plant extract was found to be more effective than lower dose. It is concluded that administration of Dolichos biflorus manifests a protective action against HFD induced oxidative stress in different tissues in rabbits and exhibits stronger antioxidant activity in in vitro studies.